Patient safety after implementation of a coproduced family centered communication programme: multicenter before and after intervention study. (5th December 2018) - Khan, Alisa; Spector, Nancy D; Baird, Jennifer D; Ashland, Michele; Starmer, Amy J; Rosenbluth, Glenn; Garcia, Briana M; Litterer, Katherine P; Rogers, Jayne E; Dalal, Anuj K; Lipsitz, Stuart; Yoon, Catherine S; et al.
Abstract: Objective: To determine whether medical errors, family experience, and communication processes improved after implementation of an intervention to standardize the structure of healthcare provider-family communication on family centered rounds. Design: Prospective, multicenter before and after intervention study. Setting: Pediatric inpatient units in seven North American hospitals, 17 December 2014 to 3 January 2017. Participants: All patients admitted to study units (3106 admissions, 13171 patient days); 2148 parents or caregivers, 435 nurses, 203 medical students, and 586 residents. Intervention: Families, nurses, and physicians coproduced an intervention to standardize healthcare provider-family communication on ward rounds ("family centered rounds"), which included structured, high reliability communication on bedside rounds emphasizing health literacy, family engagement, and bidirectional communication; structured, written real-time summaries of rounds; a formal training programme for healthcare providers; and strategies to support teamwork, implementation, and process improvement. Main outcome measures: Medical errors (primary outcome), including harmful errors (preventable adverse events) and non-harmful errors, modeled using Poisson regression and generalized estimating equations clustered by site; family experience; and communication processes (eg, family engagement on rounds). Errors were measured via an established systematic surveillance methodology including family safety reporting. Results: The overall rate of medical errors (per 1000 patient days) was unchanged (41.2 (95% confidence interval 31.2 to 54.5) pre-intervention v 35.8 (26.9 to 47.7) post-intervention, P=0.21), but harmful errors (preventable adverse events) decreased by 37.9% (20.7 (15.3 to 28.1) v 12.9 (8.9 to 18.6), P=0.01) post-intervention. Non-preventable adverse events also decreased (12.6 (8.9 to 17.9) v 5.2 (3.1 to 8.8), P=0.003). Top box (eg, "excellent") ratings for six of 25 components of family reported experience improved; none worsened. Family centered rounds occurred more frequently (72.2% (53.5% to 85.4%) v 82.8% (64.9% to 92.6%), P=0.02). Family engagement 55.6% (32.9% to 76.2%) v 66.7% (43.0% to 84.1%), P=0.04) and nurse engagement (20.4% (7.0% to 46.6%) v 35.5% (17.0% to 59.6%), P=0.03) on rounds improved. Families expressing concerns at the start of rounds (18.2% (5.6% to 45.3%) v 37.7% (17.6% to 63.3%), P=0.03) and reading back plans (4.7% (0.7% to 25.2%) v 26.5% (12.7% to 7.3%), P=0.02) increased. Trainee teaching and the duration of rounds did not change significantly. Conclusions: Although overall errors were unchanged, harmful medical errors decreased and family experience and communication processes improved after implementation of a structured communication intervention for family centered rounds coproduced by families, nurses, and physicians. Family centered care processes may improve safety and quality of care without negatively impacting teaching or duration of rounds. Trial registration: ClinicalTrials.gov NCT02320175 .